Al-doped β-NiS Mesoporous Nanoflowers for Hybrid-type Electrodes toward Enhanced Electrochemical Performance. (10th May 2017) - Ruan, Yunjun; Zha, Dace; Lv, Lin; Zhang, Bao; Liu, Jia; Ji, Xiao; Wang, Chundong; Jiang, Jianjun
Graphical abstract: Highlights: Aluminum nitrate induces growth of flowerlike Ni-Al subcarbonate. Al-doped mesoporous β-NiS are prepared by sulfidation of Ni-Al precursor. The β-NiS electrode delivers a high specific capacity and well cycling stability. The β-NiS//AC hybrid supercapacitor exhibits high energy and power densities. Abstract: Transition metal sulfides such as NiS and Co9 S8 are gaining popularity in electrochemical capacitors owning to low-cost, earth-abundant, and environmentally friendly nature, but their specific capacity/capacitance should be further improved. Here, by doping Al atoms into β-NiS mesoporous nanoflowers, we achieve reversible specific capacity of 697.3C g −1 at a current density of 1 A g −1, while the pure β-NiS electrode only delivers a specific capacity of 311.5C g −1 . The improved performance of Al-doped β-NiS could be assigned to its large surface area and mesoporous characteristics, providing abundant electroactive sites and shortening ions transport pathway. Besides, new observed multiple electrochemical redox reactions are also deem as another possible reason to enrich the electrochemical redox species for the improved electrochemical performance caused by Al doping. Theoretical calculation manifests that charges are transferred from Al atoms to both Ni and S atoms that are close to Al atoms, resulting in the appearance of Ni ions-based multiple redox reactions. Moreover, a hybrid supercapacitor composed of Al-doped NiS positive electrode and carbon-based negative electrode is configured, delivering a high energy density of 39.6 W h kg −1 at a power density of 918.8 W kg −1 . Even at a high power density of 12296 W kg −1, an energy density of 11.4 W h kg −1 can be still achieved, indicating its great potential for practical applications. Our developed doping approach may reverse the lagging status of nickel sulfides towards high theoretical-capacity capacitors.